Assessment of hemp hurd-derived biochar produced through different thermochemical processes and evaluation of its potential use as soil amendment. Issue 4 (April 2023) - Puglia, Marco; Morselli, Nicolò; Lumi, Marluce; Santunione, Giulia; Pedrazzi, Simone; Allesina, Giulio
Abstract: Biochar is a carbon-rich and porous material that finds application in different sectors and can be extremely useful in agriculture as soil improver. This paper provides a comparison between biochars produced with different slow pyrolysis processes and biochar produced in a downdraft gasifier. A blend of residual lignocellulosic biomasses (hemp hurd and fir sawdust) was pelletized and used as starting feedstock for the tests. The biochars produced were analyzed and compared. Temperature proved to be the main driver in conditioning the chemical-physical characteristics of the biochars more than residence time or the configuration of the pyrolysis process. The higher the temperature, the higher the carbon and ash content and the biochar pH and the lower the hydrogen content and the char yield. The most noticeable differences between pyrolysis and gasification biochars were the pH and the surface area (considerably higher for gasification char) and the low content of hydrogen in the gasification biochar. Two germinability tests were carried out to assess the possible application of the various biochars as soil amendment. In the first germinability test, watercress seeds were placed in direct contact with the biochar, while in the second they were placed on a blend of soil (90%v/v) and biochar (10%v/v). The biochars with the best performance were those produced at higher temperatures using a purging gas and the gasification biochar (especially mixed with soil).